Examining quantum algorithms for quantum image processing - Li, HaiSheng, 1974- (Advances in computer and electrical engineering (ACEE) book series., 2021)
"This book provides a comprehensive introduction to quantum image algorithms to establish frameworks of quantum image processing"--